Blood Donors in Iceland: A Nationwide Population-Based Study in 2005-2013 - Vigdís Jóhannsdóttir 1966- (2015)
In this study we leveraged on nationwide data to determine the size of the blood donor group in Iceland and describe its demographic- and donation characteristics. In particular we sought to describe all newly registered and regular whole blood donors in the country during the period 2005-2013. Data on the blood donors were based on information from the computer system in the Icelandic Blood Bank. Data on the Icelandic source population were retrieved from the publicly available population statistics from The Bureau of Statistics in Iceland. Following, the findings could be used to develop sound strategies for recruitment and retention of the donor group in Iceland. Our results indicate that the number of regular whole blood donors and donations decreased by 12.2% and 13.0%, respectively, from 2005 to 2013. The sexes were almost equally represented, as newly registered donors during the period, i.e. on average 47.5% females versus 52.5% males. However males (73.3%) were better represented as regular whole blood donors than females (26.7%). The mean age of newly registered donors was 29.2 years and the majority of newly registered donors were in the youngest age group, 18-25 years (51.7%). The mean age of whole blood donors was 38.6 years and the majority was in the age groups group 26-40 year (34.7%) and 41-55 year (35.1%). Only 57.3% of newly registered donors in 2005-2006, came back to donate at least once in the period 2005-2013. During the period 2005-2013 on average of 5.1% of the general population in Iceland, aged 18-69 years, donated whole blood or other blood components at least once. Even though the whole blood donor group and number of donations have declined in recent years, the supply seems to have been according to demand. Thus, use of blood components within hospitals is likely to have become more efficient during this period. However, according to population forecasts in Iceland, the need to increase the number of blood donors is foreseeable, as the age of the nation continues to rise. Smaller ...